Social services for elderly people from Romania - Chirugu, Gianina (Technium Social Sciences Journal, 2023)
The physiological limitations and fragility, but also the specific needs of the aging phenomenon, make seniors one of the vulnerable groups benefiting from social services and which together with social insurance benefits have as common purpose to cover the needs and risks associated with old age. Thus, the purpose of the paper is to define and present the system of social services for the elderly in Romania, and among the main objectives is to present the importance of social services for the elderly, the need for social services for seniors, but also to present the typology of social services provided to seniors. The methodology used for this work is the analysis of documents in particular of the legislation in force in Romania. The results obtained from the theoretical study highlight both the necessity of social services for seniors and their importance for ensuring the quality of life of the elderly in our country.